Pastoral and Monumental : Dams, Postcards, and the American Landscape - Jackson, Donald C. (Donald Conrad), 1953- (Book collections on Project MUSE., 2013)
This book chronicles America's longtime love affair with dams as represented on picture postcards from the late nineteenth to the mid-twentieth century. Through nearly four hundred images, the author documents the remarkable transformation of dams and their significance to the environment and culture of America.